Mediterranean Diet and Metabolic Diseases - Chourdakis, Michael; Magriplis, Emmanuella (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Dear Colleagues, There is increasing interest regarding the protective effect of dietary patterns on a series of metabolic diseases as compared to specific food items and nutrients, since it is well accepted that foods act synergistically. In recent years, the Mediterranean diet (MD) has gained popularity as one such dietary pattern, demonstrated to deliver many benefits according to a variety of different studies (cohort, RCT, etc.), adding to its legacy. The intention of this Special Issue is to stimulate sharing of additional clues that may further develop our understanding of the relationship between the Mediterranean diet and metabolic diseases. Another aim is to clarify potential differences in the benefits observed by different MD patterns. Moreover, as more info becomes available on the effect of MD patterns in the microbiome but also in the area of proteomics and epigenetics, relevant mechanisms and involved key mediators still need to be identified in order to provide further clarity in the description of the underlying mechanisms and the potential health outcomes occurring in response to adhering to MD. You are cordially invited to submit proposals for manuscripts that bring new elements into this interesting and promising topic. We invite clinicians and researchers to submit relevant scientific work from epidemiological or clinical studies, either original articles or reviews, to this Special Issue of Nutrients entitled "Mediterranean Diet and Metabolic Diseases".